Mobile citizenship : spatial privilege and the transnational lifestyles of senior citizens - Fauser, Margit, 1972- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Mobile Citizenship addresses the crucial question of how mobility reconfigures citizenship. Engaging with debates on transnationalism, citizenship and lifestyle migration, the book draws on ethnographic research and interview material collected among retired lifestyle migrants moving south from Germany to Turkey to explore the practices and narratives of these privileged migrants. Revealing the ways in which these migrants relate to their old homes and to their new places, the author examines the social, political and spatial dimensions of citizenship and belonging and argues that citizenship is key to understanding the privileges of transnational lifestyles. By taking up discussions emanating from studies on other privileged lifestyle migrations around social welfare and wellbeing, social participation and affective belonging, as well as class and racialized privileges, the book exposes particular comparative value and showcases similarities and differences across this emerging type of migration. Mobile Citizenship thus shows how citizenship allows for mobility, resources and privilege, yet is also replete with limitations and ambivalences. The book brings together perspectives on citizenship, space and privilege and will appeal to social scientists with interests in lifestyle migration and citizenship and their interconnections with global and social inequalities"--
Part 1: Citizenship, space and ageing -- Citizenship in the age of mobility -- Reverse spatialities -- Locating retirement lifestyle migration -- Part 2: Privileges of citizenship -- Citizenship, welfare, and well-being across borders -- Transnational lifestyles, citizenship practices, and local belonging -- Part 3: Mobile citizenship in insecure times -- Paradise lost?
OCLC-licensed vendor bibliographic record.
Keywords: World citizenship -- Case studies; Older immigrants -- Germany -- Case studies; Older immigrants -- Turkey -- Case studies; Place attachment -- Germany -- Case studies; Place attachment -- Turkey -- Case studies; Transnationalism -- Case studies; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General; Mobile citizenship